DINAMIKA RANTAI NILAI GLOBAL DALAM STRATEGI PENINGKATAN DAYA SAING INDUSTRI KAROSERI NASIONAL - , Muhammad Muharram Lubis, Drs. Riza Noer Arfani, MA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The focus of this study is the value chains dynamic in national autobody industry. National autobody industry are faced with global shift automarket and the global automotive industry structure. This study was divided into three value chain